Estudo das propriedades ópticas e estruturais de nanocristais de ZnS, obtidos pelo método solvotérmico aquecido por microondas - Santana, Yuri Vinicius Bruschi de (2013)
This work deals with the synthesis, characterization and study of nanostructures of zinc sulfide (ZnS) synthesized by microwave heated solvothermal method The synthesis method employed was extremely efficient leading to obtain the cubic and hexagonal structures of ZnS in shorter times and lower temperatures than those reported in the literature. Some synthesis parameters such as, synthesis time, temperature, and capping agent, were investigated in order to check the influence of these parameters on optical and structural properties of ZnS. The characterizations of the samples were performed by X-ray diffraction, absorption spectroscopy in the Uv-Vis, scanning electron microscopy, transmission electron microscopy and photoluminescence spectroscopy. Theoretical calculations were performed in collaboration to help explain the results. The results showed structural differences in the samples as well as different degrees of order-disorder in the material, directly related to certain parameters of synthesis. These differences were interpreted as the responsible for the modifications of the photoluminescent property.